Conceptualization, Risk Factors and Psychosocial Effects Associated with Work Addiction: A Systematic Literature Review - Diaz, Daniela (2025)
Introductión: Work addiction, or workaholism, is a behavioral addiction linked to significant physical, mental, and social health problems. Although not recognized in the Diagnostic and Statistical Manual of Mental Disorders (DSM), its conceptualization has emerged from research addressing psychological, personality, psychosocial, and organizational determinants. Objectives: This review analyzes the concept of work addiction, differentiates it from work engagement and overcommitment, identifies predisposing factors, and examines its psychosocial effects. Methodology: Following Cochrane Collaboration guidelines, a qualitative review of empirical articles published between 2019 and 2024 in English and Spanish was conducted in selected academic databases. Inclusion/exclusion criteria were applied, and the process was summarized in a PRISMA flow diagram. Discussion and Conclusions: Findings show that work addiction is influenced by personal (e.g., personality traits, neurobiology), organizational (e.g., workload, role conflict, lack of balance policies), and societal (e.g., cultural values, economic pressures, hyperconnectivity) factors. It is distinct from engagement and overcommitment, although overlaps exist. Work addiction is an underrecognized psychosocial problem with consequences such as stress, burnout, and risk of other addictions. The lack of studies in Latin America underscores the need for region-specific research to inform prevention and intervention strategies.